Feasibility and reliability of point-of-care pocket-size echocardiography performed by medical residents - Mjølstad, Ole Christian (Oxford University Press, 2013)
AIMS: To study the feasibility and reliability of pocket-size hand-held echocardiography (PHHE) by medical residents with limited experience in ultrasound. METHODS AND RESULTS: A total of 199 patients admitted to a non-university medical department were examined with PHHE. Six out of 14 medical residents were randomized to use a focused protocol and examine the heart, pericardium, pleural space, and abdominal large vessels. Diagnostic corrections were made and findings were confirmed by standard diagnostics. The median time consumption for the examination was 5.7 min. Each resident performed a median of 27 examinations. The left ventricle was assessed to satisfaction in 97% and the pericardium in all patients. The aortic and atrioventricular valves were assessed in at least 76% and the abdominal aorta in 50%, respectively. Global left-ventricular function, pleural, and pericardial effusion showed very strong correlation with reference method (Spearman's r ≥ 0.8). Quantification of aortic stenosis and regurgitation showed strong correlation with r = 0.7. Regurgitations in the atrioventricular valves showed moderate correlations, r = 0.5 and r = 0.6 for mitral and tricuspid regurgitation, respectively, similar to dilatation of the left atrium (r = 0.6) and detection of regional dysfunction (r = 0.6). Quantification of the abdominal aorta (aneurysmatic or not) showed strong correlation, r = 0.7, while the inferior vena cava diameter correlated moderately, r = 0.5. CONCLUSION: By adding a PHHE examination to standard care, medical residents were able to obtain reliable information of important cardiovascular structures in patients admitted to a medical department. Thus, focused examinations with PHHE performed by residents after a training period have the potential to improve in-hospital diagnostic procedures.